Detection of Adolescent Idiopathic Scoliosis among Nepalese Children Through the School Screening Program - Pokharel, Rohit Kumar; Lakhey, Rajesh Bahadur; Kafle, Dinesh; Shah, Lakahn Lall (Nepal Orthopaedic Association Journal, 2014)
Introduction: Idiopathic Adolescent Scoliosis (IAS) is the commonest type of scoliosis without any known cause. There has been studies in different countries and population on IAS; and its prevalence rate varies for different population. There has been no reported study done in Nepal on prevalence of adolescent idiopathic scoliosis (AIS). The aim of this study was to detect and evaluate the prevalence of idiopathic adolescent scoliosis in school children in different parts of Nepal. Methods: This was a descriptive cross sectional study conducted at five schools from different geographical parts of Nepal, from January 2010 to December 2010. Scoliosis screening was done in 5 schools from different geographical locations of Nepal. Children (from grade 6 to 10; age more than 10 years) with positive Adam’s forward bending test and scoliometer angle of 5 degrees or more were subjected for radiographic evaluation of the spine. The criterion for the diagnosis of scoliosis was detection of Cobb’s angle of more than 10 degrees. Evaluation of scoliosis according to the age, gender, ethnic group, spinal region and magnitude of curve was done. Results: Out of 1094 children screened, 31 (2.83%) were referred for radiological evaluation; and 12 of them had lateral spinal curvature of more than 10 degrees. Hence the prevalence of scoliosis was 1.09%. The girl to boy ratio of distribution of scoliosis was 3:1 for larger curves of more than 20 degrees. Maximum number of scoliosis cases was seen in girls of 13 years, and the right sided thoracic scoliosis was most common. There is no ethnic predominance of scoliosis. Conclusion: Prevalence of idiopathic scoliosis among school children who need treatment in Nepal is low; however, school screening program has its epidemiological value. DOI: http://dx.doi.org/10.3126/noaj.v3i2.9514   NOAJ July-December 2013, Vol 3, Issue 2, 14-19